ANALISIS ANTREAN BUS KOTA DI TERMINAL INDUK PURABAYA SURABAYA - Priyambodo, Richy; Sugito, Sugito; Suparti, Suparti (Jurnal Gaussian, 2012)
Transportation is an important factor to grow the economy of a region. This is because the more smoothly transport then the faster the economy growth of a region. For that, Purabaya bus station always try to provide optimum service to avoid long queue. Queue process is a process of the coming of a customer to a service facility, then waiting in line (queue) when the officers busy, and leaving the place after getting the service. If the queue at Purabaya bus station is pretty much, it will reduce the amount of revenue generated by the transport service provider. Therefore, we need a model of the queue to optimize service to customers in Purabaya bus station. From the analysis, the best queuing models obtained on the service system in Purabaya bus station is (M/G/c): (GD/∞/∞) to service system at the postal arrival with 5 counters, service system for each bus line in passenger service post is (M/G/1): (GD/∞/∞), and (G/G/2): (GD/∞/∞) to service system at the postal departure.